PHYSICOCHEMICAL AND HEDONIC CHARACTERISTICS OF MANGROVE TEA (SONNERATIA SP.) FORMULATED WITH FOUR TYPES OF SWEETENERS AND CONSUMER PREFERENCES - Sumartini, Sumartini; Hasibuan, Nabila Syakirah; Hasibuan, Nirmala Efri; Soeharso, Agusta Putri Balqis Linda; lailatussifa, RR Radipta (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Mangrove tea (Sonneratia sp.) is a promising herbal beverage due to its high bioactive content; however, its acceptance remains limited because of its astringent taste and distinctive mangrove aroma. This study aimed to analyze the effects of four types of sweeteners white sugar, palm sugar, coconut sugar, and honey on the physicochemical characteristics and consumer acceptance of mangrove tea, as well as to determine the best treatment. The research was conducted using a formulation of 3 g of mangrove leaf powder infused in 200 mL of water with sweeteners added according to each treatment, followed by measurements of pH, color (L, a, b*), viscosity, total titratable acidity, total sugar, and a hedonic test involving 30 untrained panelists. The results showed that honey had the greatest influence on the physicochemical attributes, indicated by the lowest pH (6.62), highest viscosity (1.32 mPa·s), and the darkest color with increased a* and b* values. Palm sugar and coconut sugar produced caramel-like color characteristics due to maillard components, whereas white sugar displayed the most neutral profile across all parameters. The hedonic evaluation revealed that palm sugar received the highest scores for taste, color, appearance, aroma, and overall liking, while white sugar obtained the lowest. Therefore, it can be concluded that the type of sweetener significantly affects the physical quality and consumer preference of mangrove tea, and the best treatment to enhance its sensory quality is the use of palm sugar.